PERANCANGAN LOOKBOOK VISUAL IDENTITY PROMOSI HOBO SKATEBOARDING PADANG - Dhede Rama Putra, Ir. Drs. Heldi, M.Si., Ph.D., Dra. Jupriani, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Hobo skateboarding is one of company that provides clothes, pants, bags, and accessories such as wallets, belts and key chains. Hobo skateboarding promotion is only done through social media Instagram, and the promotional efforts carried out are still not effective.The lookbook design as a visual identity and print media that makes it easier for consumers to choose a product, price, size, and communication and communicative information material, which is expected to increase Hobo skateboarding popularity and produce a positive image for consumers. The purpose of the design is to provide direct information and visualization of Skateboard Hobo products designed in a complete and communicative manner so that the information delivered can be accessed easily to attract customers to buy available products.The method used is design thinking with the analysis used is SWOT analysis, Strength, Weakness, Oppurtunity, and Threat. to find a solution to the problem. The design process starts from observation, documentation and interviews with Hobo skateboard business owners to get the data needed in the design of an effective lookbook and the clarity of information needed will be a guide in the design of the lookbook, supporting media used to support the main search media poster, T-shirts, member cards, stickers, sales invoices and shopping bags.Keywords: lookbook, visual identity, promotion